2011
DOI: 10.1161/circgenetics.111.959577
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Variation in the Association of Lipid-Related Genetic Variants With Blood Lipids in the US Adult Population

Abstract: Background-Genome-wide association studies (GWAS) have identified a number of single-nucleotide polymorphisms (SNPs) associated with serum lipid level in populations of European descent. The individual and the cumulative effect of these SNPs on blood lipids are largely unclear for the US population. Methods and Results-Using data from the second phase (1991)(1992)(1993)(1994) of the Third National Health and Nutrition Examination Survey (NHANES III), a nationally representative survey of the US population, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…Given these previously established positive outcomes of the rs5882 SNP of CETP on cardiovascular health and reduced risk of memory decline and dementia, it is surprising that our study found an increase in log(nHcy) values with this SNP. However, individual SNPs may have very small effects, but the cumulative effect of many SNPs may help to explain some of the variance in phenotype (43), so understanding the protective role of the rs5882 SNP is of further research interest.…”
Section: Discussionmentioning
confidence: 99%
“…Given these previously established positive outcomes of the rs5882 SNP of CETP on cardiovascular health and reduced risk of memory decline and dementia, it is surprising that our study found an increase in log(nHcy) values with this SNP. However, individual SNPs may have very small effects, but the cumulative effect of many SNPs may help to explain some of the variance in phenotype (43), so understanding the protective role of the rs5882 SNP is of further research interest.…”
Section: Discussionmentioning
confidence: 99%
“…Like other recent methods based on summary statistics, [10][11][12][13][14][15][16][17][18][19][20][21] our approach supplements summary association data with linkage disequilibrium (LD) information from external reference panels, avoids privacy concerns, and is scalable to hundreds of thousands of individuals and millions of markers. Unlike traditional approaches that focus on the similarity of GWAS results, [22][23][24][25][26] we use the entire spectrum of GWAS associations while accounting for LD to avoid filtering correlated SNPs.…”
Section: Introductionmentioning
confidence: 99%
“…This difference can be seen in NHANES, a dataset designed to be representative of the US population: mean TG was 113, 143, and 158 mg/dl in AA, EA, and Mexican Americans (MA), respectively, and mean HDL-C was 54, 50, and 47 mg/dl in AA, EA, and MA, respectively [4]. Notably, interethnic differences have been observed in children, providing compelling evidence that this difference is unlikely to be explained completely by variation in environmental factors by ethnicity.…”
Section: Introductionmentioning
confidence: 99%